2010
DOI: 10.2478/s10146-009-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary vitamin E and zinc on performance, oxidative stability and some blood measures of broiler chickens reared under heat stress (35 °C)

Abstract: Influence of dietary vitamin E and zinc on performance, oxidative stability and some blood measures of broiler chickens reared under heat stress (35 °C)This study was conducted to determine the effects of vitamin E (αTA; dL-α-Tocopheryl acetate) and zinc (Zn; ZnCl2) on performance, oxidative stability and some blood measures of broiler chickens under normal and hot temperatures. One hundred sixty 10-day-old male chicks were assigned to four groups in four replicates. The birds received two diets, control and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
5
19
2
5
Order By: Relevance
“…(2008), Hosseini Mansoub et al (2010 and Tawfeek etal. (2014) they reported that heat stress enhances lipid metabolism associated with the increase in serum total cholesterol (TC) and triglyceride (TG).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2008), Hosseini Mansoub et al (2010 and Tawfeek etal. (2014) they reported that heat stress enhances lipid metabolism associated with the increase in serum total cholesterol (TC) and triglyceride (TG).…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress causes an increase in free radicals by starting lipid peroxidation in cell membranes and the release of stress hormones that directly influence glucose and lipid metabolisms as well as protein catabolism (Hosseini-Mansoub et al, 2010;Imik et al, 2013).Therefore, poultry production suffers significant economic losses every year because of heat stress such as high morbidity and mortality, reduced growth rate and immune suppression (Utomo et al, 1994) and (Star et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hosseini-Mansoub et al (2010), the combination of 100 mg kg -1 of vitamin E + 50 mg kg -1 zinc is a strategy for broilers reared under heat stress, as it favors the growth performance. Nevertheless, Lopes et al (2015) claimed that levels of zinc and vitamin E above the commonly used do not improve the feed intake, weight gain, feed conversion, production viability and the production efficiency index of broilers kept under high temperatures reared on reused litter.…”
Section: Referencesmentioning
confidence: 99%
“…Reduction of glucocorticoids secretion may limit the lipid catabolism and the lipolysis (Hajati et al 2016). Likewise, Hosseini-Mansoub et al (2010) found that the antioxidant (vitamin E+zinc) supplementation to diets of broiler chickens reared under thermoneutral and high temperature significantly decreased serum cholesterol and triglyceride levels compared to diet without antioxidant supplementation. Morever, Sujatha et al (2010) indicated that polyherbal premix supplementation to broiler diets exposed to HS significantly reduced plasma cholesterol.…”
Section: Plasma Biochemistry Parametersmentioning
confidence: 99%
“…HS causes an increase in free radicals by starting lipid peroxidation in cell membranes and the release of stress hormones that directly influence glucose and lipid metabolisms as well as protein catabolism (Hosseini-Mansoub et al, 2010;Imik et al, 2013). Increasing concentrations of corticosterone were parallel to increases in serum glucose, triglyceride and cholesterol concentrations (Sahin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%